Between Folk and Lore: Performing, Textualising and (mis)Interpreting the Irish Oral Tradition - Vito, Carrassi (University of Basilicata, Italy, 2018)
Folklore, as a historical and cultural process producing and transmitting beliefs, stories, customs, and practices, has always thrived and evolved in the broader context of history and culture. Consequently, tradition and modernity have long coexisted and influenced one another, in particular in the world of folk narratives, orality and literature, storytellers and writers. Since the nineteenth century, folklorists (a category including a variety of figures) have collected, transcribed and published pieces of oral tradition, thus giving folklore a textual form and nature. However, folk narratives continue to be also a living and performed experience for the tradition bearers, a process giving rise to ever new and different expressions, according to the changing historical, social, cultural, and economic conditions. To be sure, folklore – and folk narrative – needs to be constantly lived and performed to remain something actually pertinent and significant, and not only within the oral and traditional contexts. Interestingly, between the nineteenth and the twentieth centuries, folklore increasingly came to be regarded as and transformed into an inheritance, a valuable, national heritage particularly fitting for those countries, such as Ireland, in search of a strong, national identity. In this light, folklore and folk narratives, beside their routine existence within their original contexts, were consciously “performed” by the official culture, which employed them in politics, education, literature, etc. In the process, it could happen that folk materials were dehistoricised and idealised, “embalmed” according to Máirtin Ó Cadhain, and even trivialised. This situation was turned into a fruitful and significant source of inspiration for the literary parody of Myles na gCopaleen (Flann O’Brien) who, in his Gaelic novel, An Béal Bocht, revealed the funny yet distressing truth of the Irish folklore being misunderstood and betrayed by the Irish themselves.